Scaramouche a romance of the French Revolution - Sabatini, Rafael (Houghton, 1959)
Annotation Scaramouche is a swashbuckling romantic adventure set during the French Revolution. A young lawyer becomes enmeshed in political turmoil, and goes into hiding as an actor with a traveling commedia dell'arte troupe. He plays the buffoon, Scaramouche. During his adventures he also becomes a master politician and swordsman, and though he is a revolutionary, circumstances force him to change sides several times. The tone of the book is set from the opening line: "He was born with a gift of laughter and a sense that the world was mad."
27015
Keywords: France -- History Revolution -- Fiction -- 1789-1799